Gaya Hidup sebagai Faktor Risiko Diabetes Melitus Tipe 2 - Murtiningsih, Made K.; Pandelaki, Karel; Sedli, Bisuk P. (Universitas Sam Ratulangi, 2021)
Abstract: Type 2 diabetes mellitus (T2DM) is a metabolic disease caused by insulin resistance and beta cell dysfunction. It is ranked as the seventh of top 10 causes of death worldwide, and the highest prevalence of cases is T2DM. The dominant lifestyle that triggers T2DM is diet and physical inactivity. This study was aimed to determine whether lifestyle was a risk factor of T2DM. This was a literature review study using two databases, namely Pubmed and Google Scholar. The keywords used were